Numerical modelling of two-scale flow dynamics - Bonar, P; Venugopal, V; Borthwick, A; Adcock, T (Tidal Energy Research Group, University of Oxford, 2016)
Summary: Two-scale actuator disc theory is shown to predict qualitatively the performance of a lateral array of tidal turbines in a depth-averaged channel model. The agreement between the numerical and analytical models is improved by extrapolating the numerical results to zero background roughness. Increasing background roughness is shown to reduce the optimal turbine spacing and increase the peak array power coefficient.